Analysis of Competence and Use of Information Technology and Its Effect on Teachers Performance - Asmarani, Ayu; Widdah, Minnah El; Putra, Darma; Fadhil, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aimed to determine the effect of competence and use of information technology on teacher performance. This type of research is quantitative. The research population of teachers at SMP Negeri 21 Batang Hari was 32 people. The data collection technique used a questionnaire (questionnaire), and the data were analyzed using descriptive analysis and inferential analysis using multiple regression analysis. The results showed that; 1) there is a positive and significant influence between competence on teacher performance; 2) there is a positive and significant effect between the use of information technology on teacher performance; 3) Simultaneously there is a positive and significant influence between competence and the use of information technology on teacher performance. By obtaining the value of R Square (coefficient of determination) of 0.865, which means the magnitude of the role or contribution of the competence variable and the use of information technology can explain the teacher performance variable of 86.5%. Where if the competence and use of information technology are getting better, the teachers' performance at SMP N 21 Batang Hari will also be better.